Effectiveness of TeleCTG in Reducing Neonatal Morbidity and Mortality: A Clinical Evaluation - Rodliya, Adzka Fahma; Mandariska, Resa Paksi; Mutiara, Mega Kurnia; Pertiwi, Mumpuni Intan; Fernandes, Angelina da Costa; Pires, Sonia da Costa (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Infant mortality remains a major public health challenge in Indonesia, with rates still exceeding the Sustainable Development Goals (SDGs) target. Digital health innovations, such as TeleCTG, have been introduced to improve accessibility and quality of maternal care by enabling remote fetal monitoring. This study aimed to evaluate the effectiveness of TeleCTG in reducing neonatal morbidity and mortality. A retrospective cohort design was conducted using secondary data from Puskesmas Pakutandang, involving 78 pregnant women at ?28 weeks of gestation or with risk factors. The exposure group consisted of 34 mothers who underwent TeleCTG examinations, while the non-exposure group included 44 mothers who received routine antenatal care without TeleCTG. Infant outcomes, including mortality and Apgar scores at 1/5/10 minutes, were analyzed using Fisher’s Exact Test and logistic regression with a 95% confidence interval. The results showed a significant association between TeleCTG use and reduced infant mortality (p=0.033; RR 1.158, 95% CI 1.030–1.302), while no significant effect was observed on Apgar scores <7 at 1/5/10 minutes (p=0.065). In conclusion, TeleCTG has the potential to lower infant mortality and support maternal health services, although further research with intrapartum monitoring is warranted to strengthen evidence of its effectiveness.